Biological and Clinical Relevance of Associated Genomic Alterations in MYD88 L265P and non-L265P–Mutated Diffuse Large B-Cell Lymphoma: Analysis of 361 Cases - Dubois, Sydney; Viailly, Pierre-Julien; Bohers, Elodie; Bertrand, Philippe; Ruminy, Philippe; Marchand, Vinciane; Maingonnat, Catherine; Mareschal, Sylvain; Picquenot, Jean-Michel; Penther, Dominique; Jais, Jean-Philippe; Tesson, Bruno; et al. (Clinical cancer research, 2017)
Purpose: MYD88 mutations, notably the recurrent gain-of-function L265P variant, are a distinguishing feature of activated B-cell like (ABC) diffuse large B-cell lymphoma (DLBCL), leading to constitutive NFκB pathway activation. The aim of this study was to examine the distinct genomic profiles of MYD88-mutant DLBCL, notably according to the presence of the L265P or other non-L265P MYD88 variants. Experimental Design: A cohort of 361 DLBCL cases (94 MYD88 mutant and 267 MYD88 wild-type) was submitted to next-generation sequencing (NGS) focusing on 34 genes to analyze associated mutations and copy number variations, as well as gene expression profiling, and clinical and prognostic analyses. Results: Importantly, we highlighted different genomic profiles for MYD88 L265P and MYD88 non-L265P–mutant DLBCL, shedding light on their divergent backgrounds. Clustering analysis also segregated subgroups according to associated genetic alterations among patients with the same MYD88 mutation. We showed that associated CD79B and MYD88 L265P mutations act synergistically to increase NFκB pathway activation, although the majority of MYD88 L265P–mutant cases harbors downstream NFκB alterations, which can predict BTK inhibitor resistance. Finally, although the MYD88 L265P variant was not an independent prognostic factor in ABC DLBCL, associated CD79B mutations significantly improved the survival of MYD88 L265P–mutant ABC DLBCL in our cohort. Conclusions: This study highlights the relative heterogeneity of MYD88-mutant DLBCL, adding to the field's knowledge of the theranostic importance of MYD88 mutations, but also of associated alterations, emphasizing the usefulness of genomic profiling to best stratify patients for targeted therapy. Clin Cancer Res; 23(9); 2232–44. ©2016 AACR.